Objective method to provide ground truth for IQA research. Issue 16 (1st August 2013) - Lu, Yanan; Xie, Fengying; Jiang, Zhiguo; Meng, Rusong
Abstract : Image quality assessment (IQA) research strongly depends upon subjective experiments to provide ground truth to train and evaluate the IQA algorithms. These subjective experiments are cumbersome and expensive. An objective method based on human visual characteristics is proposed to generate the ground truth for distortion images. The proposed metric called Normalised Objective Distortion Score (NODS), using the logarithm of distortion parameter as the image quality score, is easily realised so that much manpower and time cost can be saved. The effectiveness of NODS has been analysed through experiments on five state‐of‐the‐art IQA algorithms, and the result shows that the NODS is stable and can work as well as the subjective score when evaluating the performance of the IQA algorithms.